Peroxisomal Multifunctional Protein 2 Deficiency Perturbs Lipid Homeostasis in the Retina and Causes Visual Dysfunction in Mice - Das, Yannick; Swinkels, Daniëlle; Kocherlakota, Sai; Vinckier, Stefan; Vaz, Frédéric M.; Wever, Eric; van Kampen, Antoine H. C.; Jun, Bokkyoo; Do, Khanh V.; Moons, Lieve; Bazan, Nicolas G.; Van Veldhoven, Paul P.; et al. (Frontiers in Cell and Developmental Biology, 2021)
Patients lacking multifunctional protein 2 (MFP2), the central enzyme of the peroxisomal β-oxidation pathway, develop retinopathy. This pathway is involved in the metabolism of very long chain (VLCFAs) and polyunsaturated (PUFAs) fatty acids, which are enriched in the photoreceptor outer segments (POS). The molecular mechanisms underlying the retinopathy remain, however, elusive. Here, we report that mice with MFP2 inactivation display decreased retinal function already at the age of 3 weeks, which is accompanied by a profound shortening of the photoreceptor outer and inner segments, but with preserved photoreceptor ultrastructure. Furthermore, MFP2 deficient retinas exhibit severe changes in gene expression with downregulation of genes involved in the phototransduction pathway and upregulation of inflammation related genes. Lipid profiling of the mutant retinas revealed a profound reduction of DHA-containing phospholipids. This was likely due to a hampered systemic supply and retinal traffic of this PUFA, although we cannot exclude that the local defect of peroxisomal β-oxidation contributes to this DHA decrease. Moreover, very long chain PUFAs were also reduced, with the exception of those containing ≥ 34 carbons that accumulated. The latter suggests that there is an uncontrollable elongation of retinal PUFAs. In conclusion, our data reveal that intact peroxisomal β-oxidation is indispensable for retinal integrity, most likely by maintaining PUFA homeostasis.